Applying Multi-core Model Checking to Hardware-Software Partitioning in Embedded Systems - Trindade, Alessandro; Ismail, Hussama; Cordeiro, Lucas (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
We present an alternative approach to solve the hardware and software partitioning problem, which uses Bounded Model Checking (BMC) based on Satisfiability Modulo Theories (SMT) in conjunction with a multi-core support using Open Multi-Processing. The multi-core approach allows initializing many verification instances based on processors cores numbers available to the model checker. Each instance checks for a different optimum value until the optimization problem is satisfied. The goal is to show that multi-core model-checking techniques can be effective, in particular cases, to find the optimal solution of the hardware-software partitioning problem. We compare the experimental results of our proposed approach with conventional algorithms.